Abscisic Acid Regulates the Root Growth Trajectory by Reducing Auxin Transporter PIN2 Protein Levels in Arabidopsis thaliana - Xie, Qijun; Essemine, Jemaa; Pang, Xiaochen; Chen, Haiying; Jin, Jing; Cai, Weiming (Frontiers in Plant Science, 2021)
The root is in direct contact with soil. Modulation of root growth in response to alterations in soil conditions is pivotal for plant adaptation. Extensive research has been conducted concerning the adjustment of root elongation and architecture in response to environmental factors. However, little is known about the modulation of the root growth trajectory, as well as its hormonal mechanism. Here we report that abscisic acid (ABA) participated in controlling root growth trajectory. The roots upon ABA treatment or from ABA-accumulation double mutant cyp707a1,3 exhibit agravitropism-like growth pattern (wavy growth trajectory). The agravitropism-like phenotype is mainly ascribed to the compromised shootward transportation of auxin since we detected a reduced fluorescence intensity of auxin reporter DR5::VENUS in the root epidermis upon exogenous ABA application or in the endogenous ABA-accumulation double mutant cyp707a1,3. We then tried to decipher the mechanism by which ABA suppressed shootward auxin transport. The membrane abundance of PIN2, a facilitator of shootward auxin transport, was significantly reduced following ABA treatment and in cyp707a1,3. Finally, we revealed that ABA reduced the membrane PIN2 intensity through suppressing the PIN2 expression rather than accelerating its degradation. Ultimately, our results suggest a pivotal role for ABA in the root growth trajectory and the hormonal interactions orchestrating this process